Development of half metallicity within mixed magnetic phase of Cu1−xCoxMnSb alloy. (20th April 2018) - Bandyopadhyay, Abhisek; Neogi, Swarup Kumar; Paul, Atanu; Meneghini, Carlo; Bandyopadhyay, Sudipta; Dasgupta, Indra; Ray, Sugata
Abstract: Cubic half-Heusler Cu1− x Co x MnSb ( ) compounds have been investigated both experimentally and theoretically for their magnetic, transport and electronic properties in search of possible half metallic antiferromagnetism. The systems (Cu, Co)MnSb are of particular interest as the end member alloys CuMnSb and CoMnSb are semi metallic (SM) antiferromagnetic (AFM) and half metallic (HM) ferromagnetic (FM), respectively. Clearly, Co-doping at the Cu-site of CuMnSb introduces changes in the carrier concentration at the Fermi level that may lead to half metallic ground state but there remains a persistent controversy whether the AFM to FM transition occurs simultaneously. Our experimental results reveal that the AFM to FM magnetic transition occurs through a percolation mechanism where Co-substitution gradually suppresses the AFM phase and forces FM polarization around every dopant cobalt. As a result a mixed magnetic phase is realized within this composition range while a nearly HM band structure is developed already at the 10% Co-doping. Absence of T 2 dependence in the resistivity variation at low T -region serves as an indirect proof of opening up an energy gap at the Fermi surface in one of the spin channels. This is further corroborated by the ab initio electronic structure calculations that suggests that a nearly ferromagnetic half-metallic ground state is stabilized by Sb- p holes produced upon Co doping.